(untitled) (Homoeopathy for All, 2024)
Various bias occurs in clinical trial research in homeopathy.Clinical trials are experiments on human beings conducted scientifically. The objective is to find out whether, when we do something to a group of people, it gives you the desired result in many of them or not? Some newly devised or modified regimen is intentionally applied to people with or without disease to find out the efficacy and safety of this regimen. Therefore, in homeopathy, clinical trials as the scientific investigation that examine and evaluate the safety and efficacy of medicine therapies in human subjects are randomly allocated to two groups, known as the “Experiment” and the “Control” group. The experimental group is given the medicine being tested and the control group is given the placebo, an inert substance in sugar pill.